Gisli Agust Gunnlaugsson: Family and Household in Iceland 1801-1930. in the relationship between demographic and socio-economic development, social legislation and family and household structures. Studia Historica Upsaliensia 154 (Uppsala, 1988). 193 s. - Fode, Henrik (Historie/Jyske Samlinger, 1991)
-